Policy audit social protection policies and urban poor LBTs in the Philippines - Lim, Anne Marie; Jordan, Charisse M. ([Brighton] Institute of Development Studies IDS, 2013)
Lesbians, bisexual women, and trans men (LBTs) living in urban slums are systematically deprived of decent jobs, humane housing conditions, and adequate health care. Today, although Philippine law does not criminalise consensual same-sex acts and the principles of equality and non-discrimination are enshrined in the Constitution, homosexuality is policed by various social institutions, including the nuclear family and the Roman Catholic Church, which often eschew any sexual behaviour that takes place outside the context of marriage and family life. This policy audit seeks to: (1) identify and analyse the sexuality content of the selected social protection policies; (2) voice the concerns and experiences of LBTs living in GALANG?s partner urban poor communities in Quezon City; (3) share and communicate the findings of this audit with an eye towards influencing the conduct of donors and national and sub-national decision-makers, including mainstream activist organisations focusing on sexuality, social justice and feminism; (4) draw cross-cutting policy lessons that can inform future advocacy and policy development; and (5) stimulate others to replicate this analysis in their own settings.
First published by the Institute of Development Studies in August 2013.
UCWS-3329g donated by Anne Lim, GALANG Philippines - March 2014
Keywords: Lesbianism -- Philippines; Gender nonconformity -- Philippines; Sex discrimination -- Philippines